Biomarkers for primary graft dysfunction after lung transplantation: a review of current evidence and future prospects - Feng, Li; Luo, Kelin; Qiu, Yu; Li, Rui; Xue, Chun; Xi, Shuaishuai; Liu, Jixian; Pei, Yuanmin; Ma, Chao (Frontiers in Physiology, 2025)
Lung transplantation remains the only effective treatment for end-stage lung disease, offering the potential to significantly prolong survival and enhance quality of life for recipients. However, primary graft dysfunction (PGD)-a severe form of lung injury occurring within the first 72 h post-transplantation-constitutes a major cause of early mortality and presents a substantial barrier to the broader clinical adoption of lung transplantation. Biomarkers, defined as specific molecules, cells, or other biological indicators detectable within or outside the body, can reflect physiological states, disease progression, or therapeutic responses. The identification of accurate and reliable biomarkers for the prediction and diagnosis of PGD is therefore critical for improving diagnostic precision and therapeutic outcomes. This review provides a comprehensive overview of recent advances in the discovery of PGD-related biomarkers, encompassing a wide range of candidates such as plasma proteins, hormones, cell-free DNA, and immunoreactive substances. The complex biomarker landscape associated with PGD involves multiple signaling pathways and cellular phenotypes. Despite ongoing research, no single biomarker has yet demonstrated sufficient predictive or diagnostic power to be used independently in clinical practice. Consequently, continued investigation is essential to validate existing biomarkers and develop optimized strategies for their integration into routine clinical application.